Improving quality of life in vasculitis patients. (29th April 2020) - Aitken, M; Basu, N
Abstract: Systemic vasculitis are a complex cluster of diseases with high associated morbidity. As disease-related mortality diminishes, the cumulative impact of poor health-related quality of life becomes more pertinent to patients than the initial pathological insult. In this article we explore health-related quality of life in ANCA-associated vasculitis, large-vessel vasculitis and therapeutic strategies that may enhance this critical outcome.